Mapping Workplace Loneliness in Remote Working Environments: Cross-Sector Evidence, Antecedents, and Organizational Implications - Helsa Amelia Nesya Ivadianty; Hamidah Nayati Utami; Ika Ruhana (Sharia Economic and Management Business Journal (SEMBJ), 2026)
Background: The proliferation of remote work has transformed organizational interaction dynamics and heightened concerns regarding employees’ social connectedness. However, the effects of remote work on workplace loneliness vary across organizational sectors and remain insufficiently understood. Therefore, this study aims to examine the impact of remote work on workplace loneliness and identify contextual risk factors influencing this relationship. Method: This study employed a systematic literature review (SLR) approach by analyzing peer-reviewed empirical studies retrieved from a major academic database. The selected articles were screened and evaluated based on predefined inclusion criteria, and the findings were synthesized to identify patterns and contextual factors associated with workplace loneliness in remote work settings. Results: The findings demonstrate that remote work produces dual effects. On one hand, flexibility and autonomy enhance employees’ perceived control and short-term well-being. On the other hand, prolonged reductions in informal social interactions weaken employees’ sense of belonging and intensify feelings of loneliness. Sectoral differences indicate that knowledge-intensive, creative, and public service sectors are more vulnerable to relational disconnection, whereas effective communication protocols and organizational support mechanisms reduce the risk of social isolation. Furthermore, individual, occupational, and institutional factors collectively shape these outcomes. Conclusion: This study concludes that workplace loneliness in remote work environments is a multidimensional phenomenon influenced by the interaction of personal, job-related, and organizational factors. By integrating fragmented evidence across sectors into a comprehensive analytical framework, the study highlights the importance of relational resources and provides practical implications for designing socially sustainable and psychologically supportive remote work arrangements.